Social and conceptual order in Koṅku - Beck, B; Beck, Brenda (1968)
﻿ Koand#x1E45;ku is the name of distinctive geographic and social region in the West Central corner of Madras State in India. The area encompasses much of the present Coimbatore District, plus parts of Salem, Madurai and Tiruchirappalli. It is roughly 8,500 square miles in extent and has a present population of about 5,000,000. Koand#x1E45;ku is comprised of a single, broad upland plain. The area ie dry and, in addition, rainfall varies greatly in quantity from year to year. The region is roughly bounded in each of the four directions by high hills, while the plain is cut into sections by three important tributaries of the Cauvery river. The peasant inhabitants can name these distinctive physical features. They further describe the area in terms of its sacred geography. Koand#x1E45;ku has seven scored hills dedicated to Murukaand#x1E49; and seven riverside temples built in the name of Cīva. The region is further identified with a long epic or ballad which recounts the folk history of the area in some detail. In the past Koand#x1E45;ku also enjoyed a distinctive political geography. It had four great titled KavuNTar families, called PaTTkkārar. and 24 internal political divisions. Each division had its own series of caste headmen and its own Cīva temple. Within the 24 political divisions or nāTu, were kirāmam, units responsible for the payment of taxes to higher authorities. It appears that it was normal for the political and economic power within a kirāmam to be controlled by a single lineage, and at tines even a single family. This lineage or family undertook to reorganize and to oversee the exploitation of land and labour resources in their area, and also to mediate outside demands. In return they enjoyed considerable local prestige. With Independence the Indian government has made minor modifications on these kirāmam areas to form Panchayats, tbe basic administrative and electoral unit today. The pattern of dominance by individual families or groups of families within the kirāmam area continues. Rural Koand#x1E45;ku is dominated by one caste, the KavuNTars. Roughly one out of every two village residents la the region belongs to this community. They own about 90% of the land and they control political power in the area. Brahmans, on the other hand, constitute only about 1% of the general population. These people are poor and they exert little influence outside their specialised ritual sphere. It is the KavuNTars who set the character of life in the region. KavuKTars are emotionally attached to their land and they openly approve of a diet which includes meat and alcohol. KavuNTar dress, KavuNTar speech, and KavuNTar ceremonies set the standard for all the service castes who are dependent on them. In addition to KavuNTars, representatives of about fifteen other important castes, and a dozen minor ones, reside in Koand#x1E45;ku. These castes are ranked by rules of ritual pollution sad social precedence into a general hierarchical order. Leaving the Brahmans to one side, the rest of Koand#x1E45;ku society was traditionally split into two vertical halves. This division largely followed caste lines, but some groups split at a subcaste level. These two groups were like moieties or ritually opposed halves. They were called the "castes of the right-hand" and the "castes of the left-hand", respectively. The first group was composed of the KavuNTars and the various castes which were economically and ritually associated with them. The right-hand castes were tied to the land and (via the KavuNTars) they largely controlled the political and economic resources of the region. [See pdf for remainder of abstract.]